Climatology and Spatiotemporal Analysis of North Atlantic Rapidly Intensifying Hurricanes (1851–2017) - Kathleen M. Benedetto; Jill C. Trepanier (Atmosphere, 2020)
In recent decades, the scientific ability to project tropical cyclone (TC) intensities and tracks has improved. Hurricanes undergoing the process of rapid intensification (RI) have created new barriers in formulating predictions of TC paths and peak velocities. Current research suggests the warming climate may produce more intense TCs with a higher probability of undergoing RI during their life cycle. The increased likelihood of rapidly intensifying TCs necessitates the development of an RI climatology spanning the current North Atlantic record. A time series count analysis suggests a significant increasing trend of RI events in the Atlantic basin by 29.1% (17%–45%) from the years 1900 to 2017. For the entire basin, the peak frequency occurs in September, followed by August, then October. Gulf of Mexico events tend to occur more regularly over June, July, August, and September, while Atlantic storms peak in August, September, and October. The onset of RI typically begins in the Western Caribbean and Gulf of Mexico, west of 85° W. The lifetime maximum intensity typically occurs in the Gulf of Mexico basin. Density analysis suggests the locations of lifetime maximum intensities (LMIs) in rapidly intensifying TCs are clustered through space. It should be noted that these results are dependent upon the HURDAT record of events. This research is necessary in order to find substantive trends in RI events that may aid future predictions of tropical cyclones; therefore, potentially decreasing the lives lost and the cost of damage that these storms are known to cause.